1994
DOI: 10.2307/3578787
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of CD45RO + Memory and CD45RO - Naive T Cells in Culture

Abstract: Radiosensitivities of various human T-cell subsets were investigated by a proliferation assay and by a single-cell gel electrophoresis assay. Each T-cell subset was purified using a cell sorter and was induced to proliferate by ionomycin and interleukin 2. Unsorted T cells showed biphasic dose-survival curves, indicating the heterogeneity of T cells in terms of radiosensitivity. Purified CD4+ helper and CD8+ killer T cells showed similar biphasic dose-survival curves. Hence both T-cell subsets were composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…In such a case, the fluorescent density of the comet became too dim to be recognized (8,14). As a result of that, apoptotic frequencies detected at 72 h by Comet assay are lower than those at 48 h, whereas apoptotic frequencies detected at 72 h by TdT assay are much higher than the frequencies at 48 h. Our results were in accordance with some others (13,15). The results indicated that the Comet assay is suitable for apoptotic detection at an early stage.…”
Section: Comparison Between Tdt and The Comet Assaysupporting
confidence: 90%
“…In such a case, the fluorescent density of the comet became too dim to be recognized (8,14). As a result of that, apoptotic frequencies detected at 72 h by Comet assay are lower than those at 48 h, whereas apoptotic frequencies detected at 72 h by TdT assay are much higher than the frequencies at 48 h. Our results were in accordance with some others (13,15). The results indicated that the Comet assay is suitable for apoptotic detection at an early stage.…”
Section: Comparison Between Tdt and The Comet Assaysupporting
confidence: 90%
“…Moreover, the cultured T-lymphocyte populations used in the present study for individual radiation sensitivity appeared to be mainly composed of memory Tlymphocytes, with more than half memory CD8 T-lymphocytes. It has been reported that memory T-lymphocytes are more radiation-sensitive than naïve T lymphocytes [Uzawa et al, 1994]. Therefore, it is possible that excessive proliferation of memory CD8 T-lymphocytes in the culture might affect the individual radiosensitivity difference that we detected with gH2AX-FCM.…”
Section: Discussionmentioning
confidence: 49%
“…Both LD and HD radiation reduced the frequency of naïve-type CD4 + and CD8 + cells, which are scarcely effective in the context of the antitumor response, thereby suggesting a similar beneficial effect on the TDLN immune state. This phenomenon, however, might merely reflect the direct detrimental activity of radiation on naïve T cells, typically highly sensitive to radiation (29).…”
Section: Discussionmentioning
confidence: 96%